2021
DOI: 10.3389/fbinf.2021.758775
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Cells and Collagen Fibers Spatial Image Analysis

Abstract: Modern technologies designed for tissue structure visualization like brightfield microscopy, fluorescent microscopy, mass cytometry imaging (MCI) and mass spectrometry imaging (MSI) provide large amounts of quantitative and spatial information about cells and tissue structures like vessels, bronchioles etc. Many published reports have demonstrated that the structural features of cells and extracellular matrix (ECM) and their interactions strongly predict disease development and progression. Computational image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…They analyzed the expression of HIF-1 alpha in NSCLC by IHC, defining as low cutoff the median staining (>5%) and as high cutoff >60%, and found that when using the latter an association with poor prognosis was significant. In a recent study of ours ( 67 ) using the same LUAD patient samples, we described in a previous study ( 20 ), we found, by multiplex immunofluorescence, that indolent and aggressive tumors did not show significant difference in neither the amount of collagen fibers nor the average fiber length. However, when we performed spatial analysis, we found that tumor cells from the indolent group were colocalized with an increased number of immune cells.…”
Section: Discussionsupporting
confidence: 64%
“…They analyzed the expression of HIF-1 alpha in NSCLC by IHC, defining as low cutoff the median staining (>5%) and as high cutoff >60%, and found that when using the latter an association with poor prognosis was significant. In a recent study of ours ( 67 ) using the same LUAD patient samples, we described in a previous study ( 20 ), we found, by multiplex immunofluorescence, that indolent and aggressive tumors did not show significant difference in neither the amount of collagen fibers nor the average fiber length. However, when we performed spatial analysis, we found that tumor cells from the indolent group were colocalized with an increased number of immune cells.…”
Section: Discussionsupporting
confidence: 64%
“…As shown in Fig 8, the current method, compared to a naïve hard thresholding (threshold equal to 5), is better suited to detect only the abnormal elements, i.e. ellipses, thresholds equal to (5,10,15,20). A possible decision could jointly consider the two criteria, i.e.…”
Section: Methodsmentioning
confidence: 90%
“…Prognostic ECM-specific signatures have already been inferred in cancer-related studies, diabetes, wound healing, and nerve repair. There is also a growing interest in the integration of cell and ECM analyses in a spatially resolved manner to further understand the interactions between cells and their matrix microenvironment (15). Our study proposes a versatile pipeline for the analysis of ECM organization in human tissue, in which a future integration of staining for cellular components can be envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…For patient stratification, we have used CANARY software as described previously 17 , 18 . The stratification was based on the SILA score—a computerized scoring system designed for predicting LUAD behavior and estimating patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors were classified as “indolent” and “aggressive” using Computer-Aided Nodule Assessment and Risk Yield (CANARY) software as described previously 17 , 18 . The stratification strategy was based on the calculation of the Score Indicative of Lung Cancer Aggression (SILA).…”
Section: Methodsmentioning
confidence: 99%